Pendekatan Kontekstual Sebagai Upaya Meningkatkan Kemampuan Siswa Kelas IX C SMP Xaverius 2 Jambi dalam Mengapresiasi Cerita Pendek - Rosmauli Sirait (Universitas Batanghari Jambi, 2019)
Bahasa Indonesia is a subject that must be followed by students from elementary school to college, including mastery of language skills that are reading, speaking, listening and writing developed Integrated. Class action research conducted to improve students ' ability to appreciate short stories with a contextual approach in class IX C of Xaverius 2 Jambi first secondary school. The study was conducted over two cycles. Each cycle takes three stages of the process, ranging from planning, action and reflection. In the first cycle, student learning results still show an average value of 56.95, while the level of activity and the creativity of students have qualitatively obtained an average value of 67.25 with the number of students who received less (below 50) value of 50% Of the number of participants/classes (18 persons). In the second cycle, indicating an increase in the number of students who gained sufficient value (55 – 70), which is from 9 (nine) people to 18 people for all categories of assessments and students who obtained a good value of 25% (9 people). Thus, the results gained indicate that through a contextual approach, students ' ability to appreciate short stories increased as expected.